زرتشت مت اور اسلام میں فرشتوں کے تصورکا تقابلی جائزہ: A Comparative Study of the concept of Angels in Zoroastrianism and Islam (Al-Qamar, 2022)
The debate of existence of angels has been continued for centuries in mythological, philosophical, and religious context. According to Zoroastrianism, angels are metaphysical beings who were created for the spiritual guidance and training of human beings. They act as a creature for link between God and His messengers. Thus, the angels are believed to be supernatural beings who act as servants of God. They are believed to act as messengers, guides, and guardians. In Zoroastrianism top angels are named as Amesha Spenta. According to Islamic point of view, angels are the creation of God. There are three types of creations of God, one is human beings, which has the central status, the second one is the jinn, and the third one is the angels. God has created all these three creatures for His worship and obedience, but Angel’s has not given free will, while Human beings and Jinn has bestowed free will, now it is up to them that they chose obedience of Allah or select the path of Satan. Angels are understood masculine in Islam.
Keywords: Zoroastrianism; Amesha Spenta; Angels; Masculine; Messengers; Jinn; Myth; Supernatural beings